Cytomegalovirus Retinitis in a Human Immunodeficiency Virus-negative Cohort: Long-term Management and Complications. (3rd September 2015) - Jeon, Sohee; Lee, Won Ki
Abstract: Purpose : To examine the clinical outcomes achieved by using intravitreal ganciclovir injections combined with systemic anti-viral therapy in treating cytomegalovirus (CMV) retinitis in patients without human immunodeficiency virus (HIV) infection. Methods : Twenty-three eyes of 15 HIV-negative patients diagnosed with CMV retinitis were included in this retrospective study. Results : The median follow-up was 68 weeks (range, 12–156), and median number of injections was 10 (range, 2–22). The retinal lesions stopped progressing within 1–2 weeks following treatment. All of the eyes showed either unchanged or ≥2 line improvements of BCVA at last visit. There was no development of CMV retinitis in a fellow eye, or recurrence in a studied eye. Systemic complications such as neutropenia were not detected. Conclusions : Intravitreal ganciclovir injections combined with systemic anti-viral treatment is a good therapeutic option for treating CMV retinitis without HIV infection. Such treatment provided favorable visual outcomes, with minimal ocular and systemic complications.